Heinrich Ernst Albers-Schönberg, 1865–1921 - Heuck, Andreas; Goller, Sophia S. (Seminars in Musculoskeletal Radiology, 2022)
This history page in the series “Leaders in Musculoskeletal Radiology” is dedicated to the memory and achievements of the German physician Heinrich Albers-Schönberg, a pioneer of radiology whose name is connected to the medical eponym Albers-Schönberg's disease, also referred to as osteopetrosis or marble bone disease.
Keywords: osteopetrosis; Albers-Schönberg's disease; marble bone disease; osteopoikilosis; radiography